Changing Consumer Behavior Influenced By Socioeconomic Challenges: The Impact of Industry 4.0 on the Market of Electrical Devices - Rumana Siddika Marufa; Md Yusuf Hossein Khan; Md. Alomgir Hossen (SocioEconomic Challenges)
The 4th industrial age triggers a new business environment. E-commerce has significantly transformed socioeconomic landscapes by reshaping traditional business models and consumer practices. It has expanded market access, allowing businesses to overcome regional constraints, hence improving sales opportunities and fostering global trade. E-commerce also has influenced employment trends by creating new job opportunities in information technology, logistics, and digital marketing, while concurrently promoting the expansion of the gig economy. As the digital economy progresses, authorities and enterprises must confront these socioeconomic effects to maximize the benefits of online commerce while alleviating any disadvantages. Nowadays, consumers change their purchase habits from traditional to online due to technological advancement. So, businesses are rapidly moving to this new phenomenon of marketplace. In Bangladesh, among other products, the electronics sector constitutes the largest sector of the online market. Therefore, this study aimed at uncovering the key elements affecting the purchase intention of electrical devices online in Bangladesh. To achieve the research target, this study follows the self-generated integrated model. The questionnaire consists of 24 items and was completed by 308 respondents. Among them, 35.4% were women and 64.6% were men. To test the proposed conceptual model, this study uses the structural equation approach. Here, SmartPLS and IBM SPSS 25 were utilized to analyze the proposed relationship in the model. After the analysis, this study discovered that e-trust and e-service quality have a strong impact on e-word of mouth and e-satisfaction, while hedonic motivation found no impact. Further, e-word of mouth and e-satisfaction are significantly increasing the purchase intention of electronics products in Bangladesh. Such findings indicate that ensuring proper quality, achieving trust, managing customer satisfaction, and electronic word of mouth enhance purchases in an online setting. This study provides significant theoretical contributions for educators and researchers, while also delivering essential insights for businessmen, policymakers, and practitioners to improve online business operations in Bangladesh, especially in the electronic goods sector, by tackling current challenges, clarifying key ambiguities, and ultimately fostering the industry's overall development and sustainability.